(untitled) (International relations and international law Journal, 2016)
In this paper the authors consider the free movement of goods, services and capital within the European Union as a case of the Great Britain. Also, an article devoted to the role of Britain in the European Union, addresses the issue of EU enlargement in 2004 and identifies the position of the Great Britain.